Hoxa9 and Meis1 cooperatively induce addiction to syk signaling by suppressing miR-146a in acute myeloid leukemia - Mohr, Sebastian; Doebele, Carmen; Comoglio, Federico; Berg, Tobias; Beck, Julia; Bohnenberger, Hanibal; Alexe, Gabriela; Corso, Jasmin; Ströbel, Philipp; Wachter, Astrid; Beißbarth, Tim; Schnütgen, Frank; et al. (Cancer cell, 2017)
The transcription factor Meis1 drives myeloid leukemogenesis in the context of Hox gene overexpression but is currently considered undruggable. We therefore investigated whether myeloid progenitor cells transformed by Hoxa9 and Meis1 become addicted to targetable signaling pathways. A comprehensive (phospho)proteomic analysis revealed that Meis1 increased Syk protein expression and activity. Syk upregulation occurs through a Meis1-dependent feedback loop. By dissecting this loop, we show that Syk is a direct target of miR-146a, whose expression is indirectly regulated by Meis1 through the transcription factor PU.1. In the context of Hoxa9 overexpression, Syk signaling induces Meis1, recapitulating several leukemogenic features of Hoxa9/Meis1-driven leukemia. Finally, Syk inhibition disrupts the identified regulatory loop, prolonging survival of mice with Hoxa9/Meis1-driven leukemia. Hox genes; PU.1; Syk; leukemia; microRNA; signal transduction